The Society Law Perception of Precertification Property Land in Takalar District - Muhammad Rustan; Hidayah Karim; Maskawati Maskawati (Budapest International Research and Critics University, 2022)
This study aimed to analyze the public's perception in the form of knowledge, understanding, and legal attitude towards land ownership certificates. This study uses primary data as the main source and secondary data as complementary, determining the purposive sampling technique. The research specifications used descriptive analysis with the type of juridical sociological research (non-doctrinal). The results of the study show that the legal perception of the community in the form of knowledge of the understanding and legal attitude of the community towards land certification is classified as a moderate category so that when administering land certificates, the community uses second parties (family, other people and BPN employees) rather than taking care of it directly from the community the land owner.